THE ANALYSIS OF THE WORKING CAPITAL LOAN (WCL) IN MANUFACTURING SECTORS IN BANTEN PROVINCE - Prabowo, Sakti; Akhmadi, Muhammad Heru; Solikin, Akhmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The manufacturing sector is one of the economic sectors that plays a crucial role in economic development in Banten Province. This study aims to identify the impacts of the People’s Business Credit (KUR) Program on the manufacturing sector in Banten Province. The methodology used in this study is input-output analysis to determine how the KUR Program may influence the economic sectors, especially the manufacturing sector in Banten Province. The study uses the input-output table released by the Statistics Bureau at the regional level. In Banten Province, there are five sectors with the highest value of KUR. These sectors are Wholesale and Retail Trade, Accommodation and Food Service Activities, Other Service Activities, manufacturing, and Real Estate Activities. The result suggests that the KUR Program may have a good influence on the flourishing of manufacturing sectors in Banten Province. The KUR Program may have the most significant impact on the manufacturing sector when the KUR Program is distributed to the manufacturing sector itself. However, the allocation of the KUR Program to other economic sectors, especially Wholesale and Retail Trade: Repair of Motor Vehicles and Motorcycles, Accommodation and Food Service Activities, and Other Service Activities, may also have significant effects on the manufacturing sector. It may indicate that the KUR Program strategy in Banten Province may be suitable to develop the manufacturing sector in Banten Province.